Numerical Methods for Nonlocal Problems - Kaya, Adem; Kaya, Adem; Tanoğlu, Gamze (Izmir Institute of Technology, 2018)
In this thesis, numerical methods for nonlocal problems with local boundary conditions from the area of peridynamics are studied. The novel operators that satisfy local boundary conditions were proposed as an alternative to the original nonlocal problems which uses nonlocal boundaries. Peridynamic theory is reformulation of continuum mechanics by integral equations for which it has some advantages over traditional partial differential equations. In peridynamic theory, a point can interact with other points within a certain distance which is called horizon and indicated by the parameter δ. In this thesis, we are particularly interested in role of the parameter δ in numerical methods for the novel problems. More precisely, we aim to show its role in condition number, discretization error and convergence factor of multigrid method.

Bu tezde, peridinamik alanında geçen yerel sınır şartlarını sağlayan yerel olmayan problemler için sayısal yöntemler çalışılmıştır. Yerel sınır şartlarını sağlayan bu yeni operatörler, yerel olmayan sınır şartlarını kullanan orjinal yerel olmayan operatörlere bir alternatif olarak tasarlanmıştır. Peridinamik teori sürekli ortamlar mekaniğinin integral denklemleri ile yeniden formülüze edilmesidir ve bu sayede kısmi diferansiyel denklemlere göre bazı avantajları vardır. Peridinamik teoride, bir nokta belirli bir uzaklık içindeki noktalar ile etkileşim içerisindedir. Bu uzaklığa horizon (ufuk) denir ve δ ile gösterilir. Bu tezde, özellikle δ parametresinin yerel olmayan problemler için sayısal yöntemlerdeki rolleriyle ilgileneceğiz. Daha kesin bir ifadeyle, δ parametresinin kondisyon sayısındaki, ayrıklaştırma hatasındaki ve multigrid metodunun yakınsaklık faktöründeki rollerini göstereceğiz.
Yerel Olmayan Problemler için Sayısal Yöntemler
Thesis (Doctoral)--Izmir Institute of Technology, Mathematics, Izmir, 2018
Includes bibliographical references (leaves: 77-81)
Text in English; Abstract: Turkish and English
Keywords: Nonlocal problems; Numerical methods